Analisis Daya Saing dan Dampak Kebijakan Pemerintah terhadap Komoditas Kelapa Sawit Rakyat - Tifany Zia Aznur (ITB AAS INDONESIA, 2021)
Various policies are undertaken to support the increase of production and export volume of palm oil products. This study aims to analyze the competitiveness and impact of government policies on palm oil commodities in West Pasaman Regency. The research was conducted by survey method on 30 samples taken intentionally through multistage purposive sampling. The data is analyzed using Policy Analysis Matrix and sensitivity analysis. The results showed that the commodity of palm oil in Pasaman Barat Regency is competitive based on competitive advantage and comparative advantage both in the form of Fresh Fruit Bunches (FFB) and Crude Palm Oil (CPO). This is evidenced by the value of Privat Cost Ratio on FFB of 0.72 and CPO of 0,86; Domestic Resource Cost Ratio on FFB of 0.66 and CPO of 0,96; the value of private profit on FFB of 87 million rupiah and CPO of 35 billion rupiah; and social profit on FFB of 122 million rupiah and CPO of 11 billion rupiah. The impact of government policy indicated that government policies are disincentive to output, protective to tradable input, and indicated a subsidy to domestic factors. This is showed by Nominal Protection Coefficient Output on FFB of 0.82 and CPO of 0.89; Nominal Protection Coefficient Input on FFB of 0.50 and CPO of 1.00; Effective Protection Coefficient on FFB of 0.93 and CPO of 0.80; Protection Coefficient on FFB of 0.71 and CPO of 3.21; and Subsidy Ratio to Produce on FFB of -0.09 and CPO of 0.09.